GEOMETRIC PROBABILITY CALCULATION FOR A TRIANGLE - Aharonyan, N.G.; Harutyunyan, H.O. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
In the paper, using a relationship between probability $P(L(ω)\subset D) $ that a random segment of length $l$ in $R^{n}$ having a common point with body $D$ entirely lying in $D$ and the covariogram of $D$, we obtain the explicit form of $P(L(ω)\subset D) $ for any triangle on the plane.
Keywords: covariogram, kinematic measure, orientation-dependent chord length distribution, convex body, triangle